2008
DOI: 10.1093/ietfec/e91-a.7.1741
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Dynamical Model of Redox Flow Battery Based on Chemical Reaction, Fluid Flow, and Electrical Circuit

Abstract: The redox (Reduction-Oxidation) flow battery is one of the most promising rechargeable batteries due to its ability to average loads and output of power sources. The transient characteristics are well known as the remarkable feature of the battery. Then it can also compensate for a sudden voltage drop. The dynamics are governed by the chemical reactions, fluid flow, and electrical circuit of its structure. This causes the difficulty of the analysis at transient state. This paper discusses the transient behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 11 publications
0
72
0
Order By: Relevance
“…This chapter discusses, transient behaviors of the RFB in a response to a load variation using the model based on chemical kinetics [7]. After introducing the model, the setting of simulation is explained.…”
Section: Current At Transient Due To Load Variationmentioning
confidence: 99%
See 3 more Smart Citations
“…This chapter discusses, transient behaviors of the RFB in a response to a load variation using the model based on chemical kinetics [7]. After introducing the model, the setting of simulation is explained.…”
Section: Current At Transient Due To Load Variationmentioning
confidence: 99%
“…An ODE model [7] is one of the more helpful tools to analyze the transient behavior. Researchers have developed several kinds of models such as empirical models, equivalent models, and ODE models to analyze transient behaviors of an RFB [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consulted references propose that the flow of electrolyte through the active layer has a high inference performance thereof [14]. In 1998, Moyabayashi et al [15] concluded that the increase in energy efficiency is essentially determined by a uniform distribution of electrolyte.…”
Section: Introductionmentioning
confidence: 99%